2005
DOI: 10.1136/bjo.2004.046813
|View full text |Cite
|
Sign up to set email alerts
|

An interinstitutional comparative study and validation of computer aided drusen quantification

Abstract: Aims: To assess the portability and clinical applicability of a software program based on Photoshop (Adobe Systems Inc, San Jose, CA, USA) for digital drusen quantification. Methods: Independent graders from the Digital Fundus Photo Reading Center of Columbia University and King's College Hospital used macular background levelling software to quantify the percentage of drusen in the central and middle Wisconsin subfields. 100 images of consecutive patients with choroidal neovascularisation in one eye and signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Nechala et al 7 reported no differences in angular measurements and linear measurements of two points in the same sagittal plane between photogrammetric measurements and direct anthropometry. Sivagnanavel et al 8 and Assunção et al 9 conducted studies to validate software packages by comparing indirect anthropometric measurements obtained with the different software, arguing that although these digital tools are based on the same theoretical principles they could generate different results.…”
Section: Introductionmentioning
confidence: 99%
“…Nechala et al 7 reported no differences in angular measurements and linear measurements of two points in the same sagittal plane between photogrammetric measurements and direct anthropometry. Sivagnanavel et al 8 and Assunção et al 9 conducted studies to validate software packages by comparing indirect anthropometric measurements obtained with the different software, arguing that although these digital tools are based on the same theoretical principles they could generate different results.…”
Section: Introductionmentioning
confidence: 99%
“…Such interobserver disagreement was also shown in many of the images in the present study. [18]. However, their method is rather complicated and lengthy (4-10 min for each image).…”
Section: Discussionmentioning
confidence: 97%
“…It has also been used in ophthalmology to quantify the amount of leakage from choroidal neovascularization [14], the size of pigment epithelium detachment [15], the severity of cataracts [16,17], the percentage of drusen [18], and the area of the peripapillary crescent [19].…”
Section: Introductionmentioning
confidence: 99%
“…Sivagnanavel et al 12 and Assunção et al 13 have proposed software validation studies to achieve comparable measurements.…”
Section: Introductionmentioning
confidence: 99%